Kreativitas dalam Pembelajaran Sejarah Abadke-21 Studi Kasus di Sma Negeri 2 Wonogiri - Anggoro Bimo Putranto; Djono Djono (Jurnal Artefak, 2026)
This study critically analyzes the conceptualization and implementation of creativity in 21st-century history education under the Kurikulum Merdeka framework. Employing a qualitative case study with a socio-constructivist perspective, data were gathered via interviews, observations, and document analysis, then processed using Miles and Huberman’s thematic analysis. The results indicate that creativity in history is a socially mediated process shaped by pedagogical design, student characteristics, and structural constraints. Furthermore, a tension exists between curriculum policy and classroom reality. The study’s novelty lies in the development of "historical creative literacy," which reconstructs creativity as an interpretive process rooted in historical thinking rather than a generic skill. This concept effectively bridges the gap between 21st-century skill requirements and the epistemological characteristics of history learning.